Noise, Worker Perception, and Worker Concentration in Timber Harvesting Activity - Efi Yuliati Yovi; Suryaningsih (Institut Pertanian Bogor (IPB University), 2011)
Timber harvesting activities are unquestionably related with high risk of work accidents and health disorders.Such activities were not only burdened the workers with heavy physical workloads due to uneasy workingenvironment, and massive work materials and tools, but also physiopsychologically burdened workers as theywere imposed with both mechanical and acoustic vibrations (noise) produced by the chainsaw. However, it is acommon practice that most of the workers still ignored the importance of the use of noise reduction devices suchas earmuff or ear plug. This study was aimed to reveal the factual effects of noise on work concentration of theworkers to provide a scientific basis in supporting efforts in improving workers’ attitude. The results confirmedthat chainsaw might produce noise during operation. Noise intensities received by both right and left ears werenot significantly different, indicating that left-handed and normal workers received similar degree of noise inboth side of ears. Further, results also showed that there was a significant difference on the perception and workconcentration of chainsaw operators versus sedentary people to the noise. These findings proved that hearingability of chainsaw operators had declined due to frequent noise exposure.Keywords: timber harvesting, physio-psychological disorder, noise, chainsaw